2012
DOI: 10.1038/nrclinonc.2012.125
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric oncology research to improve clinical care

Abstract: Summary The incidence of cancer increases with advanced age. The Cancer and Aging Research Group (CARG), in partnership with the National Institute on Aging and National Cancer Institute, held a conference in September of 2010 which summarized the gaps in knowledge in geriatric oncology and recommendations to close these gaps. One recommendation was that the comprehensive geriatric assessment (CGA) should be incorporated within geriatric oncology research. The information from the CGA can be used to stratify p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 51 publications
0
63
1
Order By: Relevance
“…Despite recognition that CGA is paramount in this setting, there is no consensus on a recommended assessment tool and how these results should be interpreted [71,75].…”
Section: Cga Versus Screening Toolsmentioning
confidence: 98%
“…Despite recognition that CGA is paramount in this setting, there is no consensus on a recommended assessment tool and how these results should be interpreted [71,75].…”
Section: Cga Versus Screening Toolsmentioning
confidence: 98%
“…Nonetheless, aging is an individualized process, bringing both physiologic and psychosocial changes that can affect tumor biology, decision-making and tolerance for cancer treatment, and ultimately outcomes (18). The prevalence of multiple chronic illnesses in the Unites States is increasing in older adults (19) and it has been observed an even higher prevalence of comorbidity in elderly cancer patients than in an age-matched control group (20,21).…”
Section: Who Are Elderly Patients?mentioning
confidence: 99%
“…Moreover, considering improvement in quality of life in developed countries with a subsequent increase of mean life expectancy, and with a discrete part of old population being affected by one or more comorbidities, it seems that a criterion purely based on age would not fit the aim of being a discriminating parameter (18).…”
Section: Who Are Elderly Patients?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, further information on the use of sorafenib in elderly patients remains warranted. In fact, due to the peculiar and specific characteristics of this patient, it has been suggested that a case-based approach to clinical investigation should be preferred in this setting as long as specific clinical trials are not conducted [9].…”
Section: Introductionmentioning
confidence: 99%